2005
DOI: 10.1099/mic.0.28004-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell lysis directed by σ E in early stationary phase and effect of induction of the rpoE gene on global gene expression in Escherichia coli

Abstract: It has been shown that Escherichia coli cells with increased expression of the rpoE gene encoding s E exhibit enhanced cell lysis in early stationary phase. Further analysis of the lysis phenomenon was performed using a transient expression system of the rpoE gene and by DNA microarray. The former analysis revealed a s E -directed cell lysis, specific for early stationary phase but not for the exponential phase. The microarray analysis with RNAs from exponential and early stationary phase cells revealed that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
82
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 45 publications
13
82
1
Order By: Relevance
“…In previous studies of E -directed cell lysis with a ΔrseA mutant in early stationary phase, the optical densities, CFU per milliliter, and release of protein into culture supernatants were examined, but E activity was not investigated (25)(26)(27). Because we had observed that mutants with reduced E activity occasionally appeared when overnight cultures of a ΔrseA strain were plated, we decided to monitor E activity using the E -dependent rpoHp3-lacZ fusion, in addition to measuring the optical density and CFU per milliliter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies of E -directed cell lysis with a ΔrseA mutant in early stationary phase, the optical densities, CFU per milliliter, and release of protein into culture supernatants were examined, but E activity was not investigated (25)(26)(27). Because we had observed that mutants with reduced E activity occasionally appeared when overnight cultures of a ΔrseA strain were plated, we decided to monitor E activity using the E -dependent rpoHp3-lacZ fusion, in addition to measuring the optical density and CFU per milliliter.…”
Section: Resultsmentioning
confidence: 99%
“…This proposal is based on observations that cultures with elevated E activity due to E overexpression or deletion of the rseA gene have lower optical densities (ODs) in early stationary phase than do isogenic wild-type cells, although the CFU per milliliter for the two strains are comparable. Cultures with elevated E activity also have higher levels of proteins released into the growth medium than wild-type cultures, suggesting that cells that are not able to form colonies have lysed (25)(26)(27).…”
mentioning
confidence: 99%
“…The lipoproteins of the E. coli BAM complex are transcriptionally regulated by s E (Dartigalongue et al, 2001;Kabir et al, 2005;Lewis et al, 2008;Rezuchova et al, 2003), an extracytoplasmic function (ECF) sigma factor that directs the transcription of chaperones, assembly factors and proteases to restore homeostasis after envelope stress . The Caulobacter genome encodes 13 ECF sigma factors (Nierman et al, 2001), and it is currently unclear which of them perform functions analogous to E. coli s E (Alvarez-Martinez et al, 2006.…”
Section: Discussionmentioning
confidence: 99%
“…After RT reaction had been performed at 40˚C for 15 min, PCR consisting of denaturing at 82˚C for 1 min, annealing at a fixed temperature, 5 degrees lower than T m , which was calculated by the rule of thumb Sequencing of pdc gene method [18], for 1 min and extension at 72˚C for 1 min was carried out using the two primers for each gene. The PCR products after 20, 25, 30 and 35 cycles for each gene were analyzed by 0.9% agarose gel electrophoresis, and the relative intensity of the products was densitometrically estimated by using a Bio-Rad molecular imager [19,20]. Under our conditions, the RNA-selective RT-PCR was able to specifically detect mRNA, because no band was observed when reverse transcriptase was omitted.…”
Section: Rt-pcr Analysismentioning
confidence: 99%